Circulating irisin levels are associated with lipid and uric acid metabolism in a Chinese population. (25th August 2015) - Tang, Shanshan; Zhang, Rong; Jiang, Feng; Wang, Jie; Chen, Miao; Peng, Danfeng; Yan, Jing; Wang, Shiyun; Bao, Yuqian; Hu, Cheng; Jia, Weiping
Summary Irisin is a novel hormone secreted by skeletal muscle after exercise, which may ameliorate insulin resistance. In this study, we aimed to explore the relationship between circulating irisin levels and type 2 diabetes mellitus (T2DM) as well as related metabolic traits in a Chinese population. A total of 203 subjects were recruited. Of these, 68 subjects with normal glucose tolerance (NGT), 63 subjects with impaired glucose regulation (IGR) and 72 subjects with new‐onset T2DM. Circulating irisin levels were measured by enzyme‐linked immunosorbent assay (ELISA). Detailed clinical investigations and biochemistry measurements were carried out in all of the subjects. Multivariate linear regression analysis was performed to assess the association between irisin levels and related metabolic characteristics. All subjects were classified into normal weight and overweight/obese subgroups according to body mass index (BMI). No significant differences in circulating irisin levels were identified among the three groups (P = 0.9741). After adjusting for covariates, multiple linear regression analysis revealed that serum irisin level was independently and significantly associated with total cholesterol (P = 0.0005), low‐density lipoprotein cholesterol (P = 0.0014), fasting fatty acids (P = 0.0402) and uric acid (P = 0.0062). By dividing the serum irisin levels into three tertile groups, the values of total cholesterol, low‐density lipoprotein cholesterol, fasting fatty acids and uric acid were all increased significantly with the increase of irisin (P < 0.05). Moreover, serum irisin levels remain closely related to total cholesterol in both normal weight and overweight/obese subgroups. Our study suggests that circulating irisin concentrations are significantly associated with lipid and uric acid metabolism in a Chinese population.